2014
DOI: 10.1186/s13023-014-0111-y
|View full text |Cite
|
Sign up to set email alerts
|

Globotriaosylsphingosine (lyso-Gb3) might not be a reliable marker for monitoring the long-term therapeutic outcomes of enzyme replacement therapy for late-onset Fabry patients with the Chinese hotspot mutation (IVS4+919G>A)

Abstract: BackgroundIn Taiwan, DNA-based newborn screening showed a surprisingly high incidence (1/875 in males and 1/399 in females) of a cardiac Fabry mutation (IVS4 + 919G > A). However, the natural course, long-term treatment outcomes and suitable biomarkers for monitoring the therapeutic outcomes of these patients are largely unknown.MethodsFabry disease (FD) patients who had received enzyme replacement therapy (ERT) for more than 1 year were enrolled in this study from December 2008 to April 2013. Periodic echocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 20 publications
(24 reference statements)
1
24
2
Order By: Relevance
“…However, the patient with IVS+919G>A mutation in our study showed undetectable level of lyso-Gb3, and Liu et al reported that lyso-Gb3 might not be a reliable biomarker for monitoring the long-term therapeutic outcomes of ERT for late-onset FD patients with the same mutation (IVS+919G>A) [14]. Recently a highsensitive assay method for measuring lyso-Gb3 in clinical samples by means of nano-liquid chromatography-tandem mass spectrometry has been developed, and it enables us to determine low level of plasma lyso-Gb3 concentration [27].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…However, the patient with IVS+919G>A mutation in our study showed undetectable level of lyso-Gb3, and Liu et al reported that lyso-Gb3 might not be a reliable biomarker for monitoring the long-term therapeutic outcomes of ERT for late-onset FD patients with the same mutation (IVS+919G>A) [14]. Recently a highsensitive assay method for measuring lyso-Gb3 in clinical samples by means of nano-liquid chromatography-tandem mass spectrometry has been developed, and it enables us to determine low level of plasma lyso-Gb3 concentration [27].…”
Section: Discussioncontrasting
confidence: 67%
“…There was no typical pathology of FD from a skin biopsy, and his plasma lyso-Gb3 level was below the detection level (<2 nmol/l) and it could not be differentiated from the normal controls. However, genetic analysis revealed an intronic mutation (IVS4+919G>A) that is known to be a Chinese hot spot mutation causing late-onset variant of FD with cardiac hypertrophy in Taiwan [13,14]. He was finally diagnosed as having advanced stage of a cardiac variant FD.…”
Section: Clinical Characteristics Of Study Populationmentioning
confidence: 99%
“…LysoGb3 was increased in all patients; however, true baseline levels were only available for five patients. A considerable drop was seen in the five patients with true baseline values, in line with earlier studies (34,35). The most prominent agalsidase effect on lysoGb3 can be found during the first year of treatment (35).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to mutations in coding regions affecting peptide sequences and possibly modifying protein structure and function, the consequences of intronic sequences are not predictable. As shown for the mid-intronic GLA mutation IVS4+919A>G, intronic variations can affect the process of alternative splicing [ 7 , 8 ]. Due to this mutation, a weak splice site can be converted, resulting in an increased recognition and the insertion of an intronic sequence into the GLA transcript leading to a cardiac phenotype of FD [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%